2012
DOI: 10.1002/ar.22456
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Development at Early Postimplantation Stage in Mouse Embryos After Preimplantation Genetic Diagnosis

Abstract: Preimplantation genetic diagnosis (PGD) is an established procedure for the genetic analysis of embryos. To assess the effect of the procedure on early embryonic development, we generated a murine experimental system, including mice implanted with biopsied in vitro cultured embryos, control mice implanted with in vitro cultured embryos without biopsy, and mice with naturally conceived embryos. Embryos at the 7.5-dpc stage were isolated from all three groups and the embryo implantation rate, the survival rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A gross morphological evaluation of developing mouse fetuses obtained following BB did not show delayed development in early pregnancy (7.5 dpc, Yang et al 2012), while reduced fetal, but not placental, weight was observed starting from 12.5 dpc (Sato et al 2014, Yao et al 2016. Of relevance, a low fetal/placental weight ratio was observed in BB conceptuses, suggesting increased risk of cardiovascular diseases later in life (Thornburg et al 2010).…”
Section: Effects Of Blastomere Biopsy On Feto-placental Developmentmentioning
confidence: 79%
See 2 more Smart Citations
“…A gross morphological evaluation of developing mouse fetuses obtained following BB did not show delayed development in early pregnancy (7.5 dpc, Yang et al 2012), while reduced fetal, but not placental, weight was observed starting from 12.5 dpc (Sato et al 2014, Yao et al 2016. Of relevance, a low fetal/placental weight ratio was observed in BB conceptuses, suggesting increased risk of cardiovascular diseases later in life (Thornburg et al 2010).…”
Section: Effects Of Blastomere Biopsy On Feto-placental Developmentmentioning
confidence: 79%
“…Though the majority of studies did not show an increased incidence of pregnancy complications following embryo biopsy, some reported that BB is associated with reduced implantation rates, increased risks of low birth weight or preterm birth (Banerjee et al 2008, Thomaidis et al 2012, Cimadomo et al 2016 and, in early childhood, with impaired cognitive and/or motor development (Banerjee et al 2008, Middelburg et al 2011, Thomaidis et al 2012, Cimadomo et al 2016, while no indication on TB pregnancy/babies are available. Research on mouse model has shown that BB is not only associated with increased pregnancy loss and reduced/delayed fetal development, but also with impaired placental functions and epigenetic defects in both fetuses and placentae (Sugawara et al 2012, Yang et al 2012, Sato et al 2014, Wu et al 2014, Yao et al 2016. Regarding TB, research on mouse model is very limited so far.…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation